2016 Guide to Nursing Certification Boards by Specialty. Issue 1 (January 2016) - Gavin, Cara
Abstract : Membership in a professional organization creates opportunities for individuals to grow in countless ways. Often, it allows us to develop new knowledge and form networks that change our lives. There are many advantages of becoming a member of a specialty organization. Each year, Dimensions of Critical Care Nursing is proud to provide an updated list of our professional nursing organizations.